Restoration plays and players an introduction - Roberts, David 1960- (Cambridge University Press, 2014)
Introducing readers to the key texts, theatrical practice and context of late seventeenth-century drama, David Roberts combines literary and theatrical approaches to show how Restoration plays were written, performed, received and printed. Structured according to the 'life cycle' of the dramatic text, this book reproduces extracts from twenty-four of the most influential Restoration plays to provide readers with a comprehensive and colourful introduction to the period's drama. Roberts encourages readers to look beyond a limited canon of established plays and practice, and to see how Restoration Drama has been revived and adapted on the modern stage. Restoration Plays and Players is of great interest to undergraduate and non-specialist readers of seventeenth-century drama, Restoration literature and theatre studies